Who Goes on Disability When Times Are Tough? The Role of Social Costs of Take-Up Among Immigrants - Delia Furtado; Kerry L. Papps; Nikolaos Theodoropoulos (Institute of Labor Economics (IZA), 2019)
Social Security Disability Insurance (SSDI) take-up tends to increase during recessions. We exploit variation across immigrant groups in the non-pecuniary costs of participating in SSDI to examine the role that costs play in applicant decisions across the business cycle. We show that immigrants from country-of-origin groups that have lower participation costs are more sensitive to economic conditions than immigrants from high cost groups. These results do not seem to be driven by variation across groups in sensitivity to business cycles or eligibility for SSDI. Instead, they appear to be primarily driven by differences in work norms across origin countries.
Keywords: E32; J61; H55; I18; 330; disability insurance; immigrants; unemployment rates; ethnic networks